Older age and obesity are associated with increased airway closure in response to methacholine in patients with asthma. Issue 7 (5th March 2019) - Kaminsky, David A.; Chapman, David G.; Holbrook, Janet T.; Henderson, Robert J.; Sugar, Elizabeth A.; Mastronarde, John; Teague, William G.; Busk, Michael; Sumino, Kaharu; Dixon, Anne E.; Wise, Robert A.; Irvin, Charles G.
ABSTRACT: Background and objective: The reduction of forced expiratory volume in 1 s (FEV1 ) in response to methacholine challenge in asthma may reflect two components: airway narrowing, assessed by the change in FEV1 /forced vital capacity (FVC), and airway closure, assessed by the change in FVC. The purpose of this study was to determine the degree and determinants of airway closure in response to methacholine in a large group of asthmatic patients participating in studies conducted by the American Lung Association‐Airways Clinical Research Centers (ALA‐ACRC). Methods: We used the methacholine challenge data from participants in five studies of the ALA‐ACRC to determine the closing index, defined as the contribution of airway closure to the decrease in FEV1, and calculated as %ΔFVC/%ΔFEV1 . Results: There were a total of 936 participants with asthma, among whom the median closing index was 0.67 relative to that of a published healthy population of 0.54. A higher closing index was associated with increased age (10‐year increments) (0.04, 95% CI = 0.02, 0.05, P < 0.005) and obesity (0.07, 95% CI = 0.03, 0.10, P < 0.001). There was no association between the closing index and asthma control. Conclusion: Our findings confirm that airway closure in response to methacholine occurs in a large, diverse population of asthmatic participants, and that increased airway closure is associated with older age and obesity. These findings suggest that therapies targeting airway closure may be important in patients with a high closing index. Abstract : Airway closure during methacholine challenge contributes importantly to airway hyperresponsiveness in asthma and is associated with older age and obesity. See related Editorial